Increasing Computational Efficiency of Pre-Crash Simulations Using Detailed and Simplified Occupant Models - Guleyupoglu, Berkan (Wake Forest University, 2018)
Active safety systems challenge the ability to evaluate occupant injury assessment through simulation as these technologies extend the window of interest in a collision from the typical 150-200 msec crash event to 1000 or more msec. Human body models (HBMs) provide researchers with information on how a human occupant could interact with safety systems as well as the risks associated with these interactions. Detailed HBMs can provide restraint system interaction data, local injury risk data and data on correlative measures of injury however the computational cost of simulations 1000 msec or greater is likely too high for practical use. During the pre-crash portion of an event a simplified version of the same model could be used and would provide kinematic information while providing significant savings in computational cost. Use of a simplified model concurrently with a detailed model would require a means to switch between the two occupant models at the time of initiation of the crash portion of an event.